2021
DOI: 10.1186/s13019-021-01744-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on complications and mortality of patients with cardiac surgery

Abstract: Objectives The purpose of this study was to assess changes in cardiovascular disease severity, types, postoperative complications and prognosis during the COVID-19 pandemic and to explore possible influencing factors. Methods A total of 422 patients were enrolled in this study, and hospitalization and short-term follow-up data were retained. The patient population included 273 men and 149 women. Patients had a median (IQR) age of 54 (45–62) years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Moreover, the demand for non-COVID care has increased, which may be the result of lockdowns, hesitancy to pursue treatment, or delay of surgery as sequelae of COVID-19 burden on healthcare systems. 30 Intensivists remain on the frontlines caring for large numbers of critically ill COVID-19 patients, while now also facing an increased number of non-COVID patients in the ICU. In the procedural realm, the optimal timing and management of tracheostomies for COVID-19 patients remains a frequent question for intensivists, surgeons, and anesthesiologists.…”
Section: Covid-19mentioning
confidence: 99%
“…Moreover, the demand for non-COVID care has increased, which may be the result of lockdowns, hesitancy to pursue treatment, or delay of surgery as sequelae of COVID-19 burden on healthcare systems. 30 Intensivists remain on the frontlines caring for large numbers of critically ill COVID-19 patients, while now also facing an increased number of non-COVID patients in the ICU. In the procedural realm, the optimal timing and management of tracheostomies for COVID-19 patients remains a frequent question for intensivists, surgeons, and anesthesiologists.…”
Section: Covid-19mentioning
confidence: 99%
“…In contrast to that, Wang et al recently reported an increase in perioperative adverse events as well as mortality in cardiac surgery patients during the pandemic. 22 However, the study has not included HTx patients but focused on valvular heart and coronary artery disease during the early phase of the pandemic instead. 22…”
Section: Discussionmentioning
confidence: 99%
“…22 However, the study has not included HTx patients but focused on valvular heart and coronary artery disease during the early phase of the pandemic instead. 22…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that complications and mortality of cardiovascular emergencies and number of severe cases had been increased during the COVID‐19 pandemic 7,8 . Moreover, in another study, postoperative mortality was higher in COVID‐19 patients who needed cardiovascular surgery, compared to the patients without COVID‐19 9 .…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that complications and mortality of cardiovascular emergencies and number of severe cases had been increased during the COVID‐19 pandemic. 7 , 8 Moreover, in another study, postoperative mortality was higher in COVID‐19 patients who needed cardiovascular surgery, compared to the patients without COVID‐19. 9 Type A aortic dissection in COVID‐19 patients seems to associate with increased severity that even with immediate and proper diagnosis, it has higher mortality.…”
Section: Discussionmentioning
confidence: 97%